Maintenance of muscle myosin levels in adult C. elegans requires both the double bromodomain protein BET-1 and sumoylation - Kate Fisher; Fiona Gee; Siyao Wang; Feng Xue; Stefan Knapp; Martin Philpott; Christopher Wells; Miriam Rodriguez; L. Basten Snoek; Jan Kammenga; Gino B. Poulin (Biology Open, 2013)
Summary Attenuation of RAS-mediated signalling is a conserved process essential to control cell proliferation, differentiation, and apoptosis. Cooperative interactions between histone modifications such as acetylation, methylation and sumoylation are crucial for proper attenuation in C. elegans, implying that the proteins recognising these histone modifications could also play an important role in attenuation of RAS-mediated signalling. We sought to systematically identify these proteins and found BET-1. BET-1 is a conserved double bromodomain protein that recognises acetyl-lysines on histone tails and maintains the stable fate of various lineages. Unexpectedly, adults lacking both BET-1 and SUMO-1 are depleted of muscle myosin, an essential component of myofibrils. We also show that this muscle myosin depletion does not occur in all animals at a specific time, but rather that the penetrance of the phenotype increases with age. To gain mechanistic insights into this process, we sought to delay the occurrence of the muscle myosin depletion phenotype and found that it requires caspase activity and MEK-dependent signalling. We also performed transcription profiling on these mutants and found an up-regulation of the FGF receptor, egl-15, a tyrosine kinase receptor acting upstream of MEK. Consistent with a MEK requirement, we could delay the muscle phenotype by systemic or hypodermal knock down of egl-15. Thus, this work uncovered a caspase- and MEK-dependent mechanism that acts specifically on ageing adults to maintain the appropriate net level of muscle myosin.